2023
DOI: 10.3390/biomedicines11041137
|View full text |Cite
|
Sign up to set email alerts
|

Catecholaminergic and Cholinergic Systems Mediate Beneficial Effect of Vortioxetine on Diabetes-Induced Neuropathic Pain

Abstract: The therapeutic potential of vortioxetine on mechanical hyperalgesia/allodynia was investigated in rats with streptozotocin-induced diabetes, and its possible mechanism of action was elucidated in this study. The obtained findings demonstrated that subacute vortioxetine treatment (5 and 10 mg/kg for 2 weeks) increased the reduced paw-withdrawal thresholds of diabetic rats both in the Randall–Selitto and Dynamic plantar tests. Moreover, the falling latencies of animals did not change in the Rota-rod assessments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 67 publications
(102 reference statements)
0
0
0
Order By: Relevance
“…The findings of this study support the clinical findings reported in the literature regarding the efficacy of Vo on NP ( 28 , 42 ). In a study conducted on diabetic rats, Yucel et al ( 43 ) showed that Vo, in addition to its neutral activity on glycemic control, significantly improved diabetes-induced hyperalgesia and allodynia responses without affecting motor coordination. Todorovic et al ( 44 ) demonstrated the potential usefulness of Vo’s analgesic effect in treating inflammatory pain.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this study support the clinical findings reported in the literature regarding the efficacy of Vo on NP ( 28 , 42 ). In a study conducted on diabetic rats, Yucel et al ( 43 ) showed that Vo, in addition to its neutral activity on glycemic control, significantly improved diabetes-induced hyperalgesia and allodynia responses without affecting motor coordination. Todorovic et al ( 44 ) demonstrated the potential usefulness of Vo’s analgesic effect in treating inflammatory pain.…”
Section: Discussionmentioning
confidence: 99%